Clinical-therapeutic Guidelines in Pediatric Glaucoma - Marieta Dumitrache; Miruna Cioboata; Alina Ciocalteu; Rodica Lascu; M. Manea (Current Progress in Medicine and Medical Research Vol. 4, 2023)
Glaucoma in children represents a heterogeneous group of eye diseases that are accompanied by an increase in intraocular pressure in new-borns, children, adolescents, with the consequent loss of vision. Glaucoma in children has multiple clinical forms: early primary congenital glaucoma (buphthalmia) and late (juvenile glaucoma), glaucoma due to associated trabeculodysgenesis, glaucoma associated with ocular malformations, with systemic diseases or syndromes and secondary glaucoma in many eye diseases due to increased post-inflammatory IOP (uveitis), postoperatively in congenital cataracts, tumours, trauma, local, general corticotherapy. Early congenital glaucoma – Buphthalmia and late present at birth, produced by an isolated trabecular dysgenesis requires immediate diagnosis and surgical treatment, otherwise blindness occurs with functional and sometimes anatomical loss of the eye. The surgical treatment is differentiated according to the evolutionary stage of glaucoma by performing goniotomy (transparent cornea), trabeculotomy (cloudy cornea), (repeated if necessary), trabeculectomy, trabeculotomy/trabeculectomy, artificial drainage systems if there is NO satisfactory post-operative tensional response. For cases with unfavourable evolution, cyclodestructive procedures with palliative results could be used. The formation process of the anterior chamber elements next to the neural crest explains the probability of developing glaucoma associated with other eye anomalies (microphthalmia), syndromes (Sturge Weber, Bourneville, Lowe) or systemic diseases. Glaucoma can be secondary to multiple eye diseases: trauma, tumours, corticotherapy, post-inflammatorily. The indication for treatment is made after the clinical diagnosis of secondary glaucoma and is the treatment of the primary condition, and according to the type of glaucoma, stage of evolution, medical and/or surgical antiglaucoma treatment is indicated. Glaucomatous pathology in children includes multiple clinical forms, with sometimes complicated clinical evolution. Correct positive and differential diagnosis, appropriate treatment, monitoring of the disease, collaboration with the family are necessary.